(3GdJWhQGJ GdfaWjI aj GdhWf GdYQHj hGdYGde eGVjG hMGVQG(B. (3L(B2s - (3SejQ(B, (3GdJfjQs ((3HjQhJ(B:s (3OGQ Gdefgd GdHfGfj(B,s, 2008)
(3gd GfJgi YUQ GdfaW , GdNWI GdeSJbHdjI ddfaW GdYQHj , cja jSJNQL GdfaW hcja jfVH ? , GMJjGWGJ GdfaW GdYQHj , GMJjGWGJ GdfaW GdYGdejI , GMJjGWGJ GdfaW aj GdhWf GdYQHj , GdGfJGL , JbOjQGJ GdSfhGJ GdJj jSJeQ ajgG GfJGL GdfaW aj GdhWf GdYQHj , JhbYGJ GSJgdGc GdWGbI aj GdhWf GdYQHj (B19900-2000 (3, GdWGbI GdeJLOOI , GdWGbI GdfhhjI , GdfaW GdNGes
(3HjHdjhZQGajG U(B.121 (3edGMb U(B. 123s
Keywords: (3GdCbdjGJs; (3GdHdOGf GdUfGYjI GdYQHjIs; (3GdWGbIs; (3GdfaWs